The expression and clinical significance of serum exosomal-long non-coding RNA DLEU1 in patients with cervical cancer - Yu Chen; Facai Cui; Xiaoyu Wu; Weifeng Zhao; Qingxin Xia (Annals of Medicine)
Background Accumulating evidence has demonstrated that the long non-coding RNA (lncRNA) lymphocytic leukaemia deletion gene 1 (DLEU1) is abnormally overexpressed in many cancer types, including cervical cancer (CC). However, the potential clinical significance of DLEU1 in serum exosomes of patients with CC remains unclear.Methods The expression of serum exosomal DLEU1 was detected by quantitative real-time polymerase chain reaction (qRT-PCR). A receiver operating characteristic (ROC) curve was plotted to evaluate the clinical diagnostic efficacy of DLEU1. The Kaplan–Meier survival curve and Cox proportional hazards model were used to assess the effect of DLEU1 on postoperative recurrence, metastasis and prognosis among patients with CC.Results Our research showed that DLEU1 expression in the serum exosomes of patients with CC was significantly upregulated compared to that in patients with cervical intraepithelial neoplasia (CIN) and healthy controls (HCs) (both p < .001). DLEU1 relative expression was significantly correlated with tumour size, cervical invasion depth, pathological grade, International Federation of Gynecology and Obstetrics (FIGO) stage and lymph node metastasis among patients with CC (p < .01 all). The combined detection of DLEU1, carbohydrate antigen 125 (CA-125) and squamous cell carcinoma (SCC) exhibited significantly higher diagnostic efficiency (p < .01). Furthermore, the overall survival (OS) and disease-free survival (DFS) of CC patients in the high DLEU1 expression group were markedly lower than those in the low DLEU1 expression group (both p < .01). Cox univariate and multivariate regression analyses indicated that DLEU1 was an independent risk factor for postoperative recurrence and metastasis in CC patients.Conclusions Our findings suggest that serum exosome DLEU1 has certain clinical value for diagnosing, monitoring recurrence and metastasis, and evaluating CC prognosis.